The Information and Communication Technology User Role: Implications for the Work Role and Inter-Role Spillover - Piszczek, Matthew M.; Pichler, Shaun; Turel, Ofir; Greenhaus, Jeffrey (Frontiers in Psychology, 2016)
Management and organization research has traditionally focused on employees’ work role and the interface between their work and family roles. We suggest that persons assume a third role in modern society that is relevant to work and organizations, namely the Information and Communication Technology User (ICTU) role. Based on role theory and boundary theory, we develop propositions about the characteristics of this role, as well as how ICTU role characteristics are related to boundary spanning activity, inter-role spillover with the work role, and work role performance. To this end, we first conceptualize the ICTU role and its associations with work and family roles. We then apply identity theory and boundary management theory to advance our understanding of how the ICTU role is related to criteria that are important to individuals and to organizations, namely self-selection into certain types of work roles and positive and negative inter-role spillover. The implications of this role for theory, research, and practice in management and organizations are discussed.